Molecular and clinical study on prevalence of feline herpesvirus type 1 and calicivirus in correlation with feline leukemia and immunodeficiency viruses - Najafi, Hamideh (Vet Res Forum, 2014)
Upper respiratory tract diseases (URTD) are common clinical problem in cats worldwide. Feline calicivirus (FCV) and feline herpesvirus type 1 (FHV-1) are the main primary pathogens. Feline immunodeficiency virus (FIV) and Feline leukemia virus (FeLV) are also among the most common infectious diseases of cats which suppress the immunity. Oropharyngeal and conjunctival swabs and blood samples were taken from 16 cats with clinical signs of URTD and 26 clinically healthy cats. PCR and RT-PCR were used to detect FHV/FIV or FCV/FeLV infections, respectively. Feline calicivirus was detected in all cats with URTD and 87.00% and 93.00% of them were positive for FIV and FeLV, respectively. Feline herpesvirus rate of infection was 43.00% in sick cats. In clinically normal cats, prevalence rates of FCV and FHV were about 50.00%, but FIV and FeLV rates (42.00% and 65.00% respectively) were higher compared to other studies. Stomatitis was observed in 50.00% of cats with URTD. The main causative agent of corneal ulcers is FHV-1, but in 50.00% of cats with corneal ulcers, FCV was detected alone. It seems new variants of Caliciviruses are the main causative agents to attack uncommon tissues like cornea, although retroviral infections may be in the background of these various signs. The high retroviral prevalence may be due to existence of large population of stray cats. This is the first molecular study of FeLV and FCV in Iran and seems that FCV and FHV prevalence rates in FIV or FeLV infected cats is more than other non-infected ones.